Simulation of circular polarized microstrip antenna for circularly polarized - synthetic aperture radar (CP-SAR) - Bastian Wahyudi; Asrizal Asrizal; Yohandri Yohandri (Department of Physics – Universitas Negeri Padang UNP, 2017)
Remote sensing technology is important to determine the geography information. Based on the sensor used, remote sensing can be divided into two types namely optical and radar. Radar-based remote sensing is more suitable for use in parts of Indonesia when compared to using an optical sensing, because of Indonesia has a large enough cloud cover. One type of radar sensor is a sensor Synthetic Aperture Radar (SAR). SAR sensors are generally operated in the linear polarization. When propagating in the ionosphere, micro wave with linear polarization will be disturbed by the effects of Faraday rotation. The impact of the effects of Faraday rotation can be reduced by emitting microwaves in circular polarization -CP. The signal quality of the CP can be described by a parameter called axial ratio. This study simulates antenna design to determine the effect of the dimensions of the antenna on the antenna characteristics. The simulation was performed by varying the length of the patch, the width of feeding and truncated junction on the patch antenna. Antenna dimension is obtained will be used as a reference in determining the dimensions of the antenna for the CP-SAR. The device used in this simulation is IE3D with the type of substrate pillar packing (NPC-H220A) with 2,17 dielectric constant of 3,2 mm thickness and loss δ = 0.0005. From the simulations, it can bestated two of research result. First, that the correlation between the length of the patch and the operating frequency of the antenna is comparable as well as the width of feeding and the input impedance. Second, the antenna dimensions are used to determine the model of the characteristics of the antenna for applications CP - SAR at 1,270 GHz operating frequency with a value of 50,54 Ω input impedance, VSWR of 1,053 and 1,1288 dB axial ratio